Pengaruh Pemahaman Pajak, Kualitas Layanan, dan Tarif Pajak Terhadap Tingkat Kepatuhan Wajib Pajak UMKM - Fauziyah, Lailiyatul; Amin, Moh.; Nandiroh, Umi (e_Jurnal Ilmiah Riset Akuntansi, 2024)
Taxes are one of the largest sources of state income in Indonesia. Taxes contribute approximately 80% of total state income when calculated in percentage form. Sources of tax revenue come from many sectors, one of which is MSMEs. It is known that there are around 67 million MSMEs in Indonesia spread across 38 provinces. However, of the large number of MSMEs, only 2.3 million MSMEs have NPWPs and not all of them regularly pay taxes. Sri Mulyani Indrawati as Minister of Finance of Indonesia stated that the low tax ratio in Indonesia is the cause of the low tax ratio because the level of public compliance in paying taxes is still low. By conducting this research to find out whether the factors of tax understanding, service quality and tax rates can influence the level of taxpayer compliance of MSME actors. A total of 120 respondents met the criteria as samples. The research method used is purposive sampling with a quantitative approach. This research uses primary data and moderated regression analysis method.Keywords: Understanding taxes, service quality, tax rates, taxpayer compliance.